'The cage of my moment': a conversation with Emma Donoghue about history and fiction - O'Neill, Ciaran; Donoghue, Emma (My University, 2019)
This conversation with the Irish author Emma Donoghue is focused on her relationship with history and fiction. Topics discussed include the relationship between scholarly research and the writing of historical fiction, the author’s sense of duty to the past. We talked about the process of writing historical fiction, and the importance (or lack of importance) of having an ‘authentic’ link to the moment, or the material that one works with. It is in this context that the author speaks of historical fiction as something that has helped her to open the ‘cage of her moment’. The conversation took place in front of a large audience at Boston College on 1 December 2018. It was held at the end of a one-day symposium on History and Fiction at Connolly House, a renowned centre for Irish Studies in the United States, and for this reason the interview concludes with a wider consideration of the author’s Irish identity and how living outside of Ireland has effected it in recent decades.
PUBLISHED
Keywords: Emma Donoghue; Irish studies; Historical fiction